2022
DOI: 10.3390/ph15081034
|View full text |Cite
|
Sign up to set email alerts
|

Residual Microscopic Peritoneal Metastases after Macroscopic Complete Cytoreductive Surgery for Advanced High-Grade Serous Ovarian Carcinoma: A Target for Folate Receptor Targeted Photodynamic Therapy?

Abstract: Despite conventional treatment combining complete macroscopic cytoreductive surgery (CRS) and systemic chemotherapy, residual microscopic peritoneal metastases (mPM) may persist as the cause of peritoneal recurrence in 60% of patients. Therefore, there is a real need to specifically target these mPM to definitively eradicate any traces of the disease and improve patient survival. Therapeutic targeting method, such as photodynamic therapy, would be a promising method for such a purpose. Folate receptor alpha (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Microscopic peritoneal metastasis is regularly present after complete cytoreductive surgery in advanced ovarian cancer patients ( 4 ). Recent reports suggested that complete cytoreductive surgery followed by locoregional therapies such as hyperthermic intraperitoneal chemotherapy (HIPEC) ( 42 , 43 ) or molecular PDT ( 44 ) could improve survival outcomes for patients with peritoneal metastasis. Additionally, our previous study has already shown that combination of PDT and EGFR-targeted therapy can enhance survival in human ovarian carcinomatosis mouse models ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic peritoneal metastasis is regularly present after complete cytoreductive surgery in advanced ovarian cancer patients ( 4 ). Recent reports suggested that complete cytoreductive surgery followed by locoregional therapies such as hyperthermic intraperitoneal chemotherapy (HIPEC) ( 42 , 43 ) or molecular PDT ( 44 ) could improve survival outcomes for patients with peritoneal metastasis. Additionally, our previous study has already shown that combination of PDT and EGFR-targeted therapy can enhance survival in human ovarian carcinomatosis mouse models ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described that 80% of epithelial ovarian cancers overexpress FRα, while this expression is low in the normal epithelial ovarian tissues [28]. Furthermore, a recent study showed that FRα was well expressed by 75% of patients with microscopic peritoneal metastases (which are the cause of peritoneal recurrence) after complete macroscopic cytoreductive surgery [29]. Moreover, levels of FRα seems to correlate with the grade of ovarian cancer and, therefore, with the overall survival rate [30].…”
Section: Introductionmentioning
confidence: 99%